(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Retail Marketing defined as “individuals or groups,acquiring, using and disposing of products, services, ideas or experiences”(Arnould, Price & Zinkha, 2004). There are numbers of different theoriesexplaining Retail Marketing (Statt, 1997; Blackwell, Minrard, and Engel, 2006;Chaudhuri, 2006) and a huge amount of literature currently exists (Grunert2002; Botonaki, Ploymeros, Tsakorodou, & Mattas, 2006; Friese, Wanke, andPlessner, 2006). There are different number of characteristics, which canimpact on Retail Marketing (Figure 1), which includes from demographicvariables to purchase and consumption behaviours.